Comparison of healing effectiveness of different debridement approaches for diabetic foot ulcers: a network meta-analysis of randomized controlled trials - Ning, Peng; Liu, Yupu; Kang, Jun; Cao, Hongyi; Zhang, Jiaxing (Frontiers in Public Health, 2023)
Objectives The choice of the debridement method is very important for the healing of diabetic foot ulcers (DFUs), but the relative effectiveness of different debridement methods in the healing of DFUs remains unclear. This study conducted a network meta-analysis of the relative healing effectiveness of different debridement methods in patients with DFUs. Methods We performed a literature search in PubMed, Embase, and Cochrane Library from database inception up to 30 June 2023 for screening randomized controlled trials on the healing effectiveness of debridement in DFUs. Outcome measures included ulcer healing rate and ulcer area reduction rate. The Cochrane Risk Bias Tool, version 2.0, was used to assess the risk of bias in the included trials. R software was used for performing statistical analysis and GraphPad Prism was used for image plotting. Results A total of 19 randomized controlled trials were included, and 900 patients with DFUs were assessed in this analysis. The proteolytic fraction from the latex of Vasconcellea cundinamarcensis (P1G10) in enzymatic debridement showed the best ulcer healing rate (SURCA = 0.919) when compared with the standard of care (SOC) group, with a mean difference (MD) and 95% confidence interval (CI) of 1.40 (0.57, 2.36). Kiwifruit extract demonstrated the best effect on the ulcer area reduction rate (SURCA = 0.931), when compared with that in the SOC group, with an MD and 95% CI of 0.47 (0.27, 0.66). Conclusion Enzymatic debridement was superior to other debridement methods in terms of ulcer healing rate and ulcer area reduction rate in patients with DFUs. However, as the quality of the included trials is low, enzymatic debridement can be used as a candidate debridement method in addition to sharp-based debridement in clinical practice. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023441715.